The Boosters - Gylfe, Axel
1908 The words and music for "The Boosters," a march and two-step dedicated to the officials of the A. Y. P. E., were written by Axel Gylfe, a photographer and musician who lived in Aberdeen. The Alaska-Yukon-Pacific Exposition (AYPE) was a world's fair held in 1909 on the campus of Seattle's University of Washington to promote the growth and prosperity of the Pacific Northwest. Axel Gylfe (1875-1918) immigrated from Sweden in 1887 with his parents. The family settled in Grays Harbor County, where Axel married Ellen Laura Phillips (1878-1933) about 1905. After Axel's death, Ellen continued his photography studio, and their oldest child, Charles Leonard Gylfe (1906-1968), became a professional musician. Caption information source: "Alaska-Yukon-Pacific Exposition (1909): Music at the Fair" Peter Blecha, historylink.org Essay 8876. 1 score (8 p.) + 1 part 10.5 x 14 in.